Electrospun biopolymer material for antimicrobial function of fresh fruit and vegetables: Application perspective and challenges. (15th January 2023) - Shi, Chong; Fang, Donglu; Huang, Chaobo; Lyu, Lianfei; Wu, Wenlong; Li, Weilin
Abstract: Fruit and vegetables are easily subjected to postharvest quality losses. Therefore, active and functional packaging materials are needed to extend the shelf life of fruit and vegetables and improve their postharvest quality. Nanocomposite packaging materials (nano-PMs) have garnered increasing attention because of their structural and functional advantages over conventional packaging materials. Compared with conventional materials, nano-PMs showed excellent thermal stability as well as mechanical, gas barrier, and antibacterial properties. Compared with traditional techniques for preparing nano-PMs, electrospinning, which is considered an emerging and powerful technique, is used to fabricate continuous polymer nanofibers with different morphologies, structures, functions, and applications. This review focuses on different biopolymer materials (proteins and polysaccharides) and biocompatible material used for electrospinning. This review summarized the application tests of different electrospun nanofibrous materials on the postharvest quality of fruit and vegetables. The electrospun nanofibers exhibited good antimicrobial properties and maintained the morphology and nutritional quality of fruit and vegetables. In addition, the antimicrobial mechanism of functional nanoparticles and natural antimicrobial agents as well as the mechanism of oxygen and ethylene scavengers are summarized. The challenges of using nano-PMs (migration, safety, and biocompatibility) and future perspective are also discussed. Highlights: Summary of electrospun nanofibers applied to fruits and vegetables. Mechanism on function of nanoparticles and natural antimicrobial agents. Safety investigation of electrospun nanofibers materials.